2018
DOI: 10.1177/1475090218792382
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of mild steel by co-deposition using Zn-ZnO-Ant hill particulate composite coating in simulated sea water

Abstract: Naval ships are constructed with mild steel. Corrosion is a major concern in a marine environment. This particular type of material degradation has recently received more attention by the marine industry. Effort is make my researchers to combat this problem. In this work, co-deposition of Zn-ZnO-Ant hill powder composite coating on mild steel was reported with the view to combat this problem. The Ant hill powder was varied from 0 to 25 g. A 10 mL of orange juice was used as an organic additive. The coating thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…This could be attributed to the fact that the MCAp covered the substrate surface, which led to rises in the high hardness values as a result of dispersive strengthening, grain rening, strain hardening, and a rise in dislocation density. A similar observation was observed in the work of Aigbodion et al 1 A 369 and 211HB were obtained as the hardness values of the coated and substrate samples respectively; this corresponded to an increase in hardness of 74.89%. A rise in hardness levels was previously observed by Zheng et al 12 3.6 Analyses electrochemical corrosion Fig.…”
Section: Xrd Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…This could be attributed to the fact that the MCAp covered the substrate surface, which led to rises in the high hardness values as a result of dispersive strengthening, grain rening, strain hardening, and a rise in dislocation density. A similar observation was observed in the work of Aigbodion et al 1 A 369 and 211HB were obtained as the hardness values of the coated and substrate samples respectively; this corresponded to an increase in hardness of 74.89%. A rise in hardness levels was previously observed by Zheng et al 12 3.6 Analyses electrochemical corrosion Fig.…”
Section: Xrd Analysissupporting
confidence: 89%
“…A similar observation has been previously reported on the materials' ability to self-lubricate. 1 The lubrication caused by the addition of MCAp, as demonstrated in the SEM image, helps reduce wear loss.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They find out that thermal stable of the coating was obtained at 900°C with improved corrosion resistance. Aigbodion et al (2018) reported on co-deposition of Zn-ZnO-Ant hill powder composite coating on mild steel. The Ant hill powder was varied from 0 g to 25 g. A 10 mL of orange juice was used as an organic additive.…”
Section: Introductionmentioning
confidence: 99%